Analisis Pengaruh Return On Assets (ROA), Kepemilikan Asing Dan Earning Per Share (EPS) Terhadap Perkembangan Harga Saham - Sri Rahayu; Christien Setiya Kesumawati; Chintia Ayu Wulanda (UNIVERSITAS RAHARJA, 2017)
This research aimed to get empirical evidence about the influence of roa, foreign ownership and eps to stock return either partially or simultaneously. The study was conducted on 10 companies in real estate and properties listed in Indonesia Stock Exchange period 2010 - 2012. In this study, there are three variables: roa, foreign ownership, and eps as independent variables and the development of the share price as the dependent variable. The results of this study indicate that (1) ROA partially not significantly affect the development of the share price; (2) partial foreign ownership significantly influence the development of the share price; (3) EPS by partial significantly influence the development of the share price; (4) roa, foreign ownership, and eps simultaneously affect the stock price developments.